Filsafat Komunikasi, Sistematika Berfikir dan Fenomena Komunikasi - Kartini; Aqil Ramadhan, Irfan; Bas Praptama, Rifky; Salsabila, Khalishah; Atsni Sudarmansyah, Halwatia Malika; Ul Jannah, Lulu; Arifin Nasution, M. Syaraqawi; Fajar, Khairul; Tadzkiya Aulia (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This article employs a literature review research method to comprehend and explore theories from various sources related to the research. The literature review is conducted through four stages, namely preparing the necessary tools, compiling a working bibliography, organizing time and readings, and recording research materials. In data collection, a search and collection method is utilized, sourcing information from various outlets such as books, journals, and previous research. Literature is critically analyzed to support recommendations and ideas. The results and discussion highlight the philosophy of communication, ontology, epistemology, axiology, and logic within the context of communication science. Focusing on the philosophy of science, ontology describes the nature of communication, epistemology discusses ways of acquiring knowledge, axiology examines the benefits of scientific knowledge and ethical values, while logic emphasizes principles of correct thinking and reasoning. The article also discusses communication phenomena, self-concept, and the functions of human communication, relating them to the evolving paradigms and theories in the realm of knowledge.